Projected Behavioral Impacts of Global Climate Change. [article]. - Evans, Gary W.
The projected behavioral impacts of global climate change emanate from environmental changes including temperature elevation, extreme weather events, and rising air pollution. Negative affect, interpersonal and intergroup conflict, and possibly psychological distress increase with rising temperature. Droughts, floods, and severe storms diminish quality of life, elevate stress, produce psychological distress, and may elevate interpersonal and intergroup conflict. Recreational opportunities are compromised by extreme weather, and children may suffer delayed cognitive development. Elevated pollutants concern citizens and may accentuate psychological distress. Outdoor recreational activity is curtailed by ambient pollutants. Limitations and issues in need of further investigation include the following: lack of data on direct experience with climate change rather than indirect assessments related to projected changes; poor spatial resolution in environmental exposures and behavioral assessments; few rigorous quasi-experimental studies; overreliance on self-reports of behavioral outcomes; little consideration of moderator effects; and scant investigation of underlying psychosocial processes to explain projected behavioral impacts. -- (from the author)
Keywords: Extreme weather; Droughts; Climate change; Floods; Storms; Temperature